P-029 Longitudinal Monitoring of Flow-diverting Stent Tissue Coverage after Implant Using Neurovascular High Frequency Optical Coherence Tomography. (22nd July 2019) - Caroff, J; Ughi, GJ; King, R; Marosfoi, M; Langan, E; Gounis, M
Abstract : Introduction: High frequency optical coherence tomography (HF-OCT) is an intra-vascular imaging modality designed for cerebrovascular anatomy. With a spatial resolution approaching 10 µm, HF-OCT can visualize the interaction between the vessel wall and neurovascular devices in great detail. 1, 2 In this study, we sought to evaluate its use to monitor tissue growth over flow diverter stents (FDS) in an arterial bifurcation rabbit model. Materials and methods: Six FDS (Pipeline Embolization devices) were deployed in 6 animals, covering the iliac bifurcation. Four animals were treated with double antiplatelet therapy (10 mg/kg aspirin and clopidogrel), 1 with aspirin (10 mg/kg) and 1 was not given any treatment. HF-OCT data were obtained at three different time points per each animal (at implant for all animals then 14 and 60 or 7 and 30 days). For each ostium section, manual segmentation was performed to quantify the percentage of the ostium surface covered by metal and tissue (figure 1A). Results: Good quality HF-OCT data sets were successfully acquired in all cases. An average of 35 sections (with a spacing between sections of approximately 70 µm) were analyzed per ostium for each time point. Between 0 and 30 days after implant, HF-OCT analysis showed a significantly higher ostium coverage when DAPT was not given. After 30 days, similar growth rates were found in the DAPT and in the aspirin group (Figure 1B). At 60 days a high 90% coverage rate was reached in both groups. Conclusions: HF-OCT enables an accurate visualization of tissue growth over time on FDS struts. HF-OCT imaging can contribute in the pre-clinical evaluation of novel neurovascular devices and, in the near-future, it could potentially contribute to a personalized care, helping the physicians in determining and modulating the ideal antiplatelet regimen for each patient. References: Chen C-J, Kumar JS, Chen SH, et al. Optical coherence tomography: future applications in cerebrovascular imaging. Stroke 2018. Gounis MJ, Ughi GJ, Marősfoi M, et al. Intravascular optical coherence tomography for neurointerventional surgery. Stroke 2018. Disclosures: J. Caroff: None. G. J. Ughi: 4; C; Gentuity LLC. 5; C; Employee of Gentuity LLC. R. King: None. M. Marosfoi: None. E. Langan: None. M. Gounis: None.